2014
DOI: 10.4103/1110-7782.139578
|View full text |Cite
|
Sign up to set email alerts
|

Left main coronary artery thrombosis revealing angio-Behçet syndrome

Abstract: Although acute myocardial infarction commonly results from coronary atherothrombosis, there are several other etiologies that should be taken initially into account, especially in young adults without significant atherosclerotic risk factors. Thrombophilia and coronary arteritis are, in this context, examples of etiologies that should be looked after. Through this article, we present a case of Behçet’s disease with arterial involvement diagnosed after myocardial infarction resulting from thrombosis of the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Vasculitis is the main mechanism of thrombosis. 8 Patients mainly present with silent myocardial ischemia, angina, myocardial infarction, or congestive heart failure .9 Myocardial ischemia caused by thrombus formation in coronary artery may be the main reason of the chest pain in our patient. The prevalence of pulmonary artery involvement is less than 5%, 10,11 and pulmonary artery involvement is strongly associated with deep vein thrombosis and right heart thrombosis.…”
Section: Discussionmentioning
confidence: 65%
“…Vasculitis is the main mechanism of thrombosis. 8 Patients mainly present with silent myocardial ischemia, angina, myocardial infarction, or congestive heart failure .9 Myocardial ischemia caused by thrombus formation in coronary artery may be the main reason of the chest pain in our patient. The prevalence of pulmonary artery involvement is less than 5%, 10,11 and pulmonary artery involvement is strongly associated with deep vein thrombosis and right heart thrombosis.…”
Section: Discussionmentioning
confidence: 65%
“…Gürkan et al (5) first reported successful results in treating a patient with a thrombus in LMCA with a tissue plasminogen activator infusion. Ayari et al have reported thrombus regression in treating a thrombus in LMCA in a patient with angio-Behçet disease via infusion of tirofiban for 48 hours (6). Sayin et al have also reported regression of a thrombus in LMCA in patients with protein C and protein S deficiency using tirofiban (7).…”
Section: Discussionmentioning
confidence: 99%
“…This complication poses several diagnostic and therapeutic challenges and occurs predominantly in male patients ( 8 , 9 ). Cases of coronary involvement in patients with BD were mainly published from Turkey, Mediterranean Basin, Middle East, and Asian countries ( 10 16 ). The age range at the time of presentation varied widely.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired microvascular function is believed to be the cause of coronary events among these patients ( 18 ). A fresh floating thrombus in otherwise angiographically normal coronary arteries has also been documented, suggesting an underlying pro-thrombotic etiology ( 10 ). External compression of a coronary artery by an aneurysmal dilation of the left sinus of Valsalva has also been reported ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation